A vortex-based hydrodynamic cavitation manufacturing platform to generate albumin microbubbles for delivery of chemotherapies to cancerous tumours - Promita Bhattacharjee; Abhijeet H. Thaker; Pratik Kumar Patel; Vivek V. Ranade; Sarah P. Hudson (Ultrasonics Sonochemistry)
A novel approach was developed to create stable protein-based microbubbles using a vortex-driven hydrodynamic cavitation device. Such microbubbles, tiny gas-filled spheres, combined with ultrasound, can enhance drug uptake leading to inhibition of cancerous cell growth, boosting the effectiveness of anti-cancer drug molecules. The optimal conditions for the fabrication of stable bovine serum albumin (BSA) microbubbles were found to be a 15 wt% bovine serum albumin (BSA) solution at 60 °C with a pH of 6 and an ionic strength of 1.0 M. This resulted in stable BSA microbubbles with an approximate diameter of 7 μm. Curcumin-encapsulated BSA microbubbles (CBMs, 63 ± 1 μM curcumin per 101⁰ microbubbles) were created using these optimised fabrication parameters as a model system for delivering chemotherapeutic agents. The maximum percentage of curcumin release from the CBMs into phosphate buffered saline with sonication (85 %) was significantly greater than without sonication (24 %). These microbubbles were then tested to assess their effectiveness in delivering curcumin to triple-negative breast cancer cells (MDAMB-231) using a cell-to-MB ratio of 1:100, an ultrasound intensity of 0.5 W/cm2, and an ultrasound exposure time of 10 s to maximise uptake. Kinetic studies demonstrated a significant enhancement in the uptake of curcumin by MDAMB-231 cells when encapsulated into the microbubbles with ultrasound application. A substantial reduction in cellular proliferation was observed in both 2D cell culture and 3D tumour spheroid models when MDAMB-231 cells were exposed to microbubbles loaded with curcumin and ultrasound was applied. The vortex-based hydrodynamic cavitation device successfully generated curcumin loaded microbubbles with a long shelf life (120 days at 4 °C), mild preparation conditions, and enhanced uptake into cancerous tumour spheroid models. This data demonstrates the potential of this device for the commercial manufacture of drug loaded microbubble-based delivery systems.